2016
DOI: 10.1007/s00223-016-0216-5
|View full text |Cite
|
Sign up to set email alerts
|

The Activity of Adiponectin in Bone

Abstract: The adipokine adiponectin affects multiple target tissues and plays important roles in glucose metabolism and whole-body energy homeostasis. Circulating adiponectin levels in obese people are lower than in non-obese, and increased serum adiponectin is associated with weight loss. Numerous clinical studies have established that fat mass is positively related to bone mass, a relationship that is maintained by communication between the two tissues through hormones and cytokines. Since adiponectin levels inversely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 64 publications
3
46
0
1
Order By: Relevance
“…Others have consistently shown circulating adiponectin levels to be inversely correlated with BMD (Naot et al. ), which we now show to be increased in low protein offspring at 6 weeks of age. It is possible the described hormonal changes were directly responsible for the changes to bone growth and development observed.…”
Section: Discussionsupporting
confidence: 79%
“…Others have consistently shown circulating adiponectin levels to be inversely correlated with BMD (Naot et al. ), which we now show to be increased in low protein offspring at 6 weeks of age. It is possible the described hormonal changes were directly responsible for the changes to bone growth and development observed.…”
Section: Discussionsupporting
confidence: 79%
“…In this regard, adiponectin levels are generally decreased in obese, insulin-resistant, and type 2 diabetes patients [16]. Extensive research has also brought to light the physiological role of Acrp30 in bone metabolism [17]. In particular, analyzing Acrp30 endocrine effects on the skeletal system in women, an inverse correlation between its serum concentration and bone mineral density (BMD) has clearly been demonstrated in different clinical studies [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have shown that ADP may regulate bone resorption and bone formation by affecting the proliferation and differentiation of osteoclasts and osteoblasts. A number of clinical observational studies have shown that ADP levels is negatively correlated with BMD, suggesting that it might be a negative regulator of bone metabolism [67], nevertheless, it still remains controversial in the study of human body. Thus, the interaction between ADP and OC on bone metabolism and glycolipid metabolism and the mechanism therein are unclear yet, which need to be further studied for a better understanding.…”
Section: Oc and Exercisementioning
confidence: 99%